Natural resource economics; conservation and exploitation - Neher, Philip A (Cambridge, 1990)
The events of our time reveal a world where people are more able than ever before to exploit their environment. There are questions about when and how to use resources and about the ability of current institutions to make the appropriate decisions concerning their allocation. Natural Resource Economics explores the positive contribution that economics can make to resolving issues of all kinds: the atmosphere, the land and water, and wild animals and plants. This book establishes a concert framework for thinking about resource allocation that borrows from the familiar microeconomic theory of the firm by elaborating the concept of capital asset management and extends these concepts to deal with the problems of resource utilization. In addition, the idea of market failures is used to justify the assertion that collective action is needed to achieve a more economical allocation of resources when ordinary markets are conspicuously inefficient. The book serves the student who wants to learn how to solve natural resource problems as opposite to merely read about them. By working with this volume the reader acquires a tool kit to formulate and solve intertemporal allocation problems. The first section offers an introduction to the main topics and introduces basic ideas to the general reader. The remaining three sections build on university and college lavel micro-economics and on the first university course in mathematics. The use of mathematics is motivated by the pressing need to confront problems that are difficult to solve with less powerful tools. Mathematical appendixes are provided to refresh the reader.
Keywords: Natural resources-management